Comunicar é aprender : as experiências de aprendizagem colaborativa via Internet entre escolas de Aracaju - Linhares, Maria Conceição da Silva (2008)
Working with ICT as mediators on knowledge construction inside the school is not an easy task and it is a collective challenge to the actors of pedagogical actions. The object of study in this dissertation is the comprehension and the analysis of the commitment and production from students and teachers through collaborative learning with the help of computer laboratories included on the Project Comunicar é aprender . The schools participating on this research are Colégio Nossa Escola, a private institution and Escola Estadual Governador Albano Franco, an institution from the public system. The analysis was performed under the theoretical and methodological basis of the Project mentioned, supported on the SocioCultural Theory of Levy S. Vygotsky and on the Linguistics, we used the perspective of Bakthin. To understand the collaborative learning through the use of ICT we researched authors such as: Crook (1998), Callegaro (2001), Espinosa (2003), Lévy (1993, 1996,) Marco Silva (2005, 2006); Moraes (2004, 2007), and others. The issues analysed on this study convey that collaborative work is a determinant factor to collaborative learning and to the cognitive development of children.